DAMPAK SOSIAL PETI BAGI KELANGSUNGAN HIDUP MASYARAKAT DI DESA TANJUNG HULU KECAMATAN SEPAUK - Octaviana, Eva; Ulfah, Maria; Harjanti, Diah Trismi (Universitas Tanjungpura, 2023)
This research is entitled Social Impact of Unlicensed Gold Mining for Community Survival in Tanjung Hulu Village, Sepauk District, Sintang Regency. Where this area is one of the places that has many illegal gold mines, the mining community still uses traditional methods and makeshift tools so that the social impact of PETI will have a major impact on the environment, but it does not rule out other positive impacts that will be felt by the community. The purpose of this study was to find out how the impact of illegal gold mining (PETI) on the people of Tanjung Hulu Village. This study uses a qualitative method with descriptive analysis. Even though the community is aware of the impact caused by PETI activities, the community is still very dependent on PETI to meet their daily needs. The location of this research is in Tanjung Hulu Village, Sepauk District, Sintang Regency. The results of this study indicate that the impact that is most visible and felt by the community is the environmental impact and the impact of the increase on the improvement of the community's economy. Factors that encourage mining communities to still carry out PETI are family economic problems, education, etc. Efforts that can be made by the government are to strengthen permits and not work on land in any place.